Budgeting: An Experimental Investigation of the Effects of Negotiation - Fisher, Joseph G.; Frederickson, James R.; Peffer, Sean A. (The Accounting Review, 2000)
Despite the common use of negotiations to set budgets in practice, accounting research has focused primarily on budgets set unilaterally by subordinates, while goal-setting research in management has focused primarily on budgets set unilaterally by superiors. In addition, budgeting research in accounting has focused almost exclusively on the planning aspects of budgets to the exclusion of their motivational aspects. This study complements prior research in two ways. First, the study examines how budgets and the economic consequences of the budget-setting process differ when budgets are set through a negotiation process vs. when set unilaterally. The study also considers factors associated with negotiation agreement and the relation between agreement and the economic consequences of negotiated budgets. Second, the economic consequences examined are budgetary slack and subordinate performance, allowing us to address the trade-offs between the planning and motivational aspects of budgets. Negotiated budgets differ from unilaterally set budgets in a manner consistent with social norms and/or information transfer occurring during negotiations. Both the budgets and the economic consequences of the budgetsetting process differ when budgets are set through a negotiation process where superiors have final authority in the event of a negotiation impasse vs. when set unilaterally by superiors. Further, negotiation agreement significantly affects the economic consequences of negotiated budgets. Budgets set through a negotiation process ending in agreement contain significantly less slack. A failed negotiation followed by superiors imposing a budget has a significant detrimental effect on subordinate performance.